The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.7150/thno.45079
|View full text |Cite
|
Sign up to set email alerts
|

ZnS@ZIF-8 core-shell nanoparticles incorporated with ICG and TPZ to enable H2S-amplified synergistic therapy

Abstract: Abnormal tumor microenvironment, such as hypoxia, interstitial hypertension and low pH, leads to unexpected resistance for current tumor treatment. The development of versatile drug delivery systems which present responsive characteristics to tumor microenvironment (TME) has been extensively carried out, but remains challenging. In this study, zeolitic imidazolate framework-8 (ZIF-8) coated ZnS nanoparticles have been designed and prepared for co-delivery of ICG/TPZ molecules, denoted as ZSZIT, for H … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 43 publications
(41 reference statements)
3
44
0
Order By: Relevance
“…Consistent with this nding, Shari , et al [6] and Shari , et al [8] showed that Dox focused more on breast cancer tissue using Fe NPs compared to the control group. However, the positive effect of using PDT on metallic NZs containing drug in tumor therapy is similar to the nding of Fang, et al [61] who showed that the effect of gas therapy to reduce drug resistance is very signi cant.…”
Section: Discussionsupporting
confidence: 78%
“…Consistent with this nding, Shari , et al [6] and Shari , et al [8] showed that Dox focused more on breast cancer tissue using Fe NPs compared to the control group. However, the positive effect of using PDT on metallic NZs containing drug in tumor therapy is similar to the nding of Fang, et al [61] who showed that the effect of gas therapy to reduce drug resistance is very signi cant.…”
Section: Discussionsupporting
confidence: 78%
“…H 2 S also could aggravate the hypoxia to activate hypoxia‐activated prodrug to enhance chemotherapy. [ 17 ] Additionally, H 2 S gas is reported to induce acute toxicity by inhibiting the activity of mitochondrial cytochrome c oxidase (COX IV). [ 18 ] COX IV is the terminal metal membrane enzyme on the electron transport chain of the mitochondrial inner membrane, and an important part of cellular aerobic respiration and generation of adenosine triphosphate (ATP).…”
Section: Introductionmentioning
confidence: 99%
“…Here, to solve this problem, a stable zeolite imidazole framework structure was introduced on the surface of Eu MOF to provide coating protection for EuMOF, while as an excellent drug loading tool due to its porosity and high speci c surface [44][45][46]. Therefore, we reported a luminescent EuMOF nanocomposite (EuMOF@ZIF/AP-PEG, named EZAP) as a multifunctional nanoplatform for microwave-thermal therapy and chemotherapy and uorescence imaging of tumors (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%